2003
DOI: 10.1523/jneurosci.23-34-10756.2003
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Toxicity in Rotenone Models of Parkinson's Disease

Abstract: Exposure of rats to the pesticide and complex I inhibitor rotenone reproduces features of Parkinson's disease, including selective nigrostriatal dopaminergic degeneration and alpha-synuclein-positive cytoplasmic inclusions (Betarbet et al., 2000; Sherer et al., 2003). Here, we examined mechanisms of rotenone toxicity using three model systems. In SK-N-MC human neuroblastoma cells, rotenone (10 nm to 1 microm) caused dose-dependent ATP depletion, oxidative damage, and death. To determine the molecular site of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

47
673
3
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 930 publications
(727 citation statements)
references
References 48 publications
47
673
3
4
Order By: Relevance
“…From these data, we inferred that MsrA failed to inhibit dopaminergic cell death or aggresome formation induced by MG132. The suppression of rotenone-induced neurodegeneration and aggresome formation by MsrA suggests that the enzyme interferes with oxidative stress triggered by complex I inhibition [43]. This result agrees with previous data showing that MsrA protects against cell death elicited by other oxidative insults [20][21][22][23].…”
Section: Msra Fails To Inhibit Dopaminergic Cell Death Elicited By Mg132supporting
confidence: 92%
See 1 more Smart Citation
“…From these data, we inferred that MsrA failed to inhibit dopaminergic cell death or aggresome formation induced by MG132. The suppression of rotenone-induced neurodegeneration and aggresome formation by MsrA suggests that the enzyme interferes with oxidative stress triggered by complex I inhibition [43]. This result agrees with previous data showing that MsrA protects against cell death elicited by other oxidative insults [20][21][22][23].…”
Section: Msra Fails To Inhibit Dopaminergic Cell Death Elicited By Mg132supporting
confidence: 92%
“…Because rotenone triggers dopaminergic cell death by causing a buildup of ROS [43], MsrA could protect against rotenone-induced neurodegeneration by (i) suppressing intracellular oxidative stress via a ROS scavenging mechanism, and/or (ii) repairing methionine-oxidized proteins. To address these mechanisms, we tested the effect of MsrA on indices of oxidative stress in rotenone-treated, primary midbrain cultures.…”
Section: Msra Suppresses Rotenone Toxicity With Little Effect On Protmentioning
confidence: 99%
“…Pesticide exposure in experimental rodent and cell culture models has been linked to ROS generation and/or an inflammatory response that potentiates ROS production. Dopaminergic toxicity by rotenone, a naturally occurring complex I inhibitor and a common herbicide, is caused by oxidative stress and is mediated, in part, by the activation of microglia (Gao et al, 2002(Gao et al, , 2003bSherer et al, 2002;Sherer et al, 2003;Zeevalk and Bernard, 2005). The neurotoxicity of paraquat (PQ), a bipyridial herbicide, mimics PD in experimental models and results in microglia activation and redox cycling via microglial NADPH oxidase (McCormack et al, 2002;Bonneh-Barkay et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Betarbet and co-workers [31,32] showed that chronic treatment with rotenone was sufficient to cause typical features of PD, including loss of dopaminergic neurons and appearance of a-syn-positive inclusions in rodents. The involvement of oxidative damage caused by mitochondrial dysfunction after rotenone treatment was also demonstrated in in vitro models, suggesting specific neuronal death by rotenone [33]. In this regard, a large number of environmental situations and agents have been identified, including farming and rural life, industrial chemicals, metals, and pesticide exposure; however, no conclusive relationships between individual studies have been found [26,34,35].…”
Section: Sporadic and Familial Forms Of Pdmentioning
confidence: 99%